China's Football Dream: Sport, Citizenship, Symbolic Power, and Civic Spaces. (December 2019) - Sullivan, Jonathan; Chadwick, Simon; Gow, Michael
This article examines the mobilization of football in relation to Chinese state-building projects. Pierre Bourdieu's concept of "symbolic power" is applied to frame policy analysis of China's 2016-2050 National Football Plan and narrative analysis of developments within China's rapidly expanding football sector. The extensive mobilization of national, provincial, and local government institutions forms spaces for civic participation in state-building projects through direct participation in football. These civic spaces allow for active citizenship engagement with state projects and for expressions of consensus and participation with the Chinese Dream while also limiting potential for competing cultural movements to emerge. This article argues that such developments are driven primarily for socio-political objectives with the aim of fostering shared notions of citizenship through the medium of sport.